2014
DOI: 10.1371/journal.pone.0086496
|View full text |Cite
|
Sign up to set email alerts
|

Neural Plasticity in Human Brain Connectivity: The Effects of Long Term Deep Brain Stimulation of the Subthalamic Nucleus in Parkinson’s Disease

Abstract: BackgroundPositive clinical outcomes are now well established for deep brain stimulation, but little is known about the effects of long-term deep brain stimulation on brain structural and functional connectivity. Here, we used the rare opportunity to acquire pre- and postoperative diffusion tensor imaging in a patient undergoing deep brain stimulation in bilateral subthalamic nuclei for Parkinson’s Disease. This allowed us to analyse the differences in structural connectivity before and after deep brain stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
93
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 56 publications
3
93
0
1
Order By: Relevance
“…We first modelled structural changes in these patients using whole-brain computational models 73 , and observed an improvement in the performance of the model compared to that of normal participants following six months of DBS of the subthalamic nucleus (Figure 4A and 4B). As shown in Figure 4C, the perturbational measures of segregation and integration were sensitive to the improvements (that is, alleviation of symptoms) following DBS.…”
Section: Characterizing Different States Of the Brain In Health And Dmentioning
confidence: 99%
“…We first modelled structural changes in these patients using whole-brain computational models 73 , and observed an improvement in the performance of the model compared to that of normal participants following six months of DBS of the subthalamic nucleus (Figure 4A and 4B). As shown in Figure 4C, the perturbational measures of segregation and integration were sensitive to the improvements (that is, alleviation of symptoms) following DBS.…”
Section: Characterizing Different States Of the Brain In Health And Dmentioning
confidence: 99%
“…Deep-brain stimulation (DBS) is a powerful clinical therapeutic tool of neuromodulation that has recently emerged as a new focus of functional neuroimaging investigations (Kahan et al, 2014;van Hartevelt et al, 2014). Neuroimaging studies with DBS in animals have focused on neurological conditions, such as epilepsy (Canals et al, 2008;Dunn et al, 2009;Jupp et al, 2006) and Parkinson's disease Lai et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The long -term DBS was found to restore local brain structural connectivity and global functional connectivity (eg, Parkinson disease). 99 The first clinical evidence that demonstrated an effective BP reduction after DBS was reported in a patient who primarily underwent a stimulation of the ventrolateral PAG/periventricular gray matter to treat his chronic central pain syndrome that was unresponsive to pain--relief drug.…”
Section: Deep Brain Stimulationmentioning
confidence: 99%
“…The long -term DBS was found to restore local brain structural connectivity and global functional connectivity (eg, Parkinson disease). 99 The first clinical evidence that demonstrated an effective BP reduction after DBS was reported in a patient who primarily underwent a stimulation of the ventrolateral PAG/periventricular gray matter to treat his chronic central pain syndrome that was unresponsive to pain--relief drug.100 While DBS alleviated pain levels for 4 months which then returned to the same level as before the procedure, there was a gradual decrease in BP up to 33 months after DBS with medication withdrawal postoperatively. These results indicated that the site in the brain (PAG) can be a target for sympathetic BP control and center for pain modulation.…”
mentioning
confidence: 99%